The Impact of Intellectual Capital Disclosure and Type of Ownership on Evaluation of a Company's Financial Performance after IPO - Dyah Arini Rudhiningtyas; Yuli Soesetio; Chois Nuril Faizza (Postgraduate Program Merdeka University, 2022)
This study aims to determine the effect of Intellectual capital Disclosure (ICD) and the type of ownership on financial performance after the IPO in short and medium period. This study uses a quantitative approach and multiple regression analysis. Data was obtained from prospectuses and financial statements of companies that conducted IPOs on Indonesia Stock Exchange for the period 2000-2015. The population in this study was all companies that conducted initial public offerings from 2000 to 2015, as many as 316 companies and 234 companies were selected as samples using purposive sampling methods. The results showed that Intellectual Capital Disclosure had a significant positive effect on short-term (1-year) and medium-term (3-year) financial performance post-IPO, however, type of ownership has no effect on short or medium-term financial performance post-IPO. These results show that the degree of intelectual capital disclosure can control the company's performance for the better. This provides broad insights for decision makers.